Quality Control in Medical Education: Global and Bangladesh Perspectives (Bangladesh Journal of Medical Biochemistry, 2013)
DOI: http://dx.doi.org/10.3329/bjmb.v3i1.13799 Bangladesh J Med Biochem 2010; 3(1): 3-5